The transformation of war in the modern world: challenges in the battle for mindspace - Sidorenko, Irina N. (Journal of the Belarusian State University. Sociology, 2026)
In this article, based on the concept of K. Clausewitz and the definition of historical types of scientific rationality by the Russian philosopher V. S. Stepin, the evolution of war was revealed and the main stages of its transformation were identified: classical, non-classical and post-non-classical wars. As selection criteria, such components as the armed forces, the territory and will of the enemy, the subject of military actions, territory, economy, front line, peace treaty and others were used. It was noted that the post-non-classical war is fundamentally different from both traditional classical wars and non-classical ones, in particular, in that, despite the variety of its definitions, it can be described as a «culturally conditioned type of activity» and is less dependent on production and economic spheres. The author of the article analyses the specifics and nature of modern war as a consciential war aimed at capturing and transforming consciousness by recoding the value system, historical memory and patterns of behaviour. The connection between the consciential war and identity politics is asserted. Possible mechanisms of countering consciential weaponry are studied.
Keywords: classical war; non-classical war; post-non-classical war; consciential war; hybrid war; post-national war; violence